Remembranzas boyacenses “una propuesta para la masificación de los ritmos autóctonos del departamento de Boyacá ” - Herrera Hernández, Luis Arcenio (Uptc, 2012)
This article comes from the pedagogical experience of Rumbambuquiando, musical group formed by students of master’s degree in Music from UPTC, who, from the first half of their career in 2005, showed great interest in the new expression of the Colombian Andean music, exploring different traditional rhythms and incorporating the traditional format (guitar, treble guitar and mandolin) instruments like the flute, the drum and bass. Group members at that time, had a marked tendency to bamcuco (Colombian popular rhythm) than to Creole rumba, hence comes the name of the group. However, from the beginning was this interest by folklore from Boyacá Department,bearing in mind that the idea of creating a group of “carranguera” music (native music of Boyacá), emerged in 2004 during an exploratory time in which were found the “requinto” (small guitar), guitar and voice.